Performance of Dual Purpose Quails Fed with Canola Oil and Organic Selenium and the Productivity Traits in their Offspring - Roll , A.P.; Pires, P.G.S.; Azambuja, S.A.; Bavaresco, C.; Roll, V.F.; Dionello, N.J.L.; Rutz, F. (International Journal of Poultry Science, 2014)
Recent results suggest that the nutrition of quail breeders could influence not only their own performance but also the performance of their progeny. To test this hypothesis the dual purpose breeders (Coturnix coturnix coturnix) were fed six dietary treatments: T1-Control; T2-Soybean oil +0.3ppm organic Se; T3-Canola oil; T4-Canola oil +0.3 ppm organic Se; T5-½ soybean oil +½ canola oil; T6-½ soybean oil +½ canola oil +0.3 ppm organic Se. The organic Se was added on top of experimental diets (30 g/100 kg). The performance of 252 was evaluated from 52 to 136 days of age. A total of 344 eggs from the quails fed the experimental diets during 84 days was incubated. Later, egg weight, egg production and body weight from the first generation offspring were evaluated. A basal corn-soybean meal diet of the progeny was the same to all birds and was formulated to contain 22% crude protein and 2780 kcal/kg/ME. A total of 167 female’s quails was hatched and their performance during the initial laying cycle (50 to 80 days of age) was evaluated. Treatment means were compared by orthogonal contrasts and Duncan’s test at 5% level. The performance of breeders was not significantly affected. The results showed differences (p